Third-generation cephalosporin resistance conferred by a chromosomally encoded blaCMY-23 gene in the Escherichia coli ST131 reference strain EC958. (18th March 2015) - Phan, Minh-Duy; Peters, Kate M.; Sarkar, Sohinee; Forde, Brian M.; Lo, Alvin W.; Stanton-Cook, Mitchell; Roberts, Leah W.; Upton, Mathew; Beatson, Scott A.; Schembri, Mark A.
Abstract: Objectives: Escherichia coli ST131 is a globally disseminated MDR clone originally identified due to its association with the bla CTX-M-15 gene encoding an ESBL. It is thus assumed that bla CTX-M-15 is the major determinant for resistance to β-lactam antibiotics in this clone. The complete sequence of EC958, a reference strain for E. coli ST131, revealed that it contains a chromosomally located bla CMY-23 gene with an upstream IS Ecp1 element as well as several additional plasmid-encoded β-lactamase genes. Here, we examined the genetic context of the bla CMY-23 element in EC958 and other E. coli ST131 strains and investigated the contribution of bla CMY-23 to EC958 resistance to a range of β-lactam antibiotics. Methods: The genetic context of bla CMY-23 and its associated mobile elements was determined by PCR and sequencing. Antibiotic susceptibility testing was performed using Etests. The activity of the bla CMY-23 promoter was assessed using lacZ reporter assays. Mutations were generated using λ-Red-recombination. Results: The genetic structure of the IS Ecp1 -IS 5 - bla CMY-23 mobile element was determined and localized within the betU gene on the chromosome of EC958 and five other E. coli ST131 strains. The transcription of bla CMY-23, driven by a previously defined promoter within IS Ecp1, was significantly higher than other β-lactamase genes and could be induced by cefotaxime. Deletion of the bla CMY-23 gene resulted in enhanced susceptibility to cefoxitin, cefotaxime and ceftazidime. Conclusions: This is the first known report to demonstrate the chromosomal location of bla CMY-23 in E. coli ST131. In EC958, CMY-23 plays a major role in resistance to third-generation cephalosporins and cephamycins.